Power generation from concentration gradient by reverse electrodialysis in anisotropic nanoporous anodic aluminum oxide membranes - Lee, Yunhyun; Jung Kim, Hyun; Kim, Dong Kwon (Energies, 2020)
In this study, reverse electrodialysis power generation using an anisotropic anodic aluminum oxide membrane with nanopores of two different pore diameters is proposed and experimentally investigated for the first time. A number of experiments were carried out for various combinations of concentrations to show that the anisotropic anodic aluminum oxide membrane is superior to the conventional isotropic membrane. As a result, the highest power density that was measured from the anisotropic membrane was 15.0 mW/m2, and it was 7.2 times higher than that from the isotropic membrane. The reasons why the anisotropic membrane is superior to the isotropic membrane are explained in detail. The experiments on the anisotropic membranes with various active layer lengths and pore diameters were also conducted for exploring the effects of these engineering parameters on the power generation performance. As a result, it was shown that the length of the active layer is a more important engineering parameter than the pore diameter of the active layer. Additionally, it was also shown that a low concentration solution should be brought into contact with the active layer side of the membrane whenever an anisotropic membrane is used for reverse electrodialysis.
Keywords: Anisotropic membrane; Anodic aluminum oxide membranes; Concentration gradients; Engineering parameters; Isotropic membrane; Low concentrations; Nanoporous membrane; Reverse electrodialysis; Anisotropic nanoporous membrane; Power generation; Reverse electrodialysis